Implementing Vocabulary Self-Collection Strategy in Teaching Vocabulary Mastery to Secondary Junior High School - Azzahra, Javita Putri; Utami, Praditya Putri (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
Vocabulary plays a vital role in mastering a foreign language, as it directly influences students’ ability to communicate effectively. However, many students still face challenges in understanding, remembering, and using new vocabulary in meaningful contexts. This study aimed to investigate the implementation of the Vocabulary Self-Collection Strategy (VSS) in improving students’ vocabulary mastery and to explore their experiences and perceptions during the learning process. The research employed a qualitative approach using a case study design. The participants were nine eighth-grade students from a junior high school in Karawang, selected through purposive sampling. Data were collected through participant observation, interviews, and exploration tasks, and analyzed using the Miles and Huberman model, which included data collection, data reduction, data display, and conclusion drawing. The findings revealed that students initially struggled to understand and retain new vocabulary due to unclear instruction, monotonous activities, and limited learning strategies. After implementing VSS, students showed increased motivation, autonomy, and critical thinking. They became more active in identifying new words, analyzing their meanings in context, and collaborating with peers during classroom discussions. The strategy also helped students develop analytical skills and promoted deeper vocabulary learning by connecting words to meaningful contexts. Overall, the implementation of VSS proved effective in enhancing students’ vocabulary mastery, fostering learner independence, and creating a more interactive and engaging classroom environment. These findings suggest that VSS can serve as an alternative approach to traditional vocabulary instruction, offering both cognitive and affective benefits for English language learners.